Residence time distribution (RTD) of water flooding activity in oil recovery using vertical sand column: Radiotracer approach. Issue 1 (March 2021) - Othman, N; Wan Kamal, W H B; Jasni, N S; Rosli, N R; Yahya, R; Yusoff, N H; Mohd Yunos, M A S; Shah Dahing, L N; Shari, M R; Hassan, H; Amahmood, A; Terry, A M; et al.
Abstract: Waterflooding is a common secondary recovery oil extraction method that can enhance oil recovery up to 45 percent overall recovery factor. Waterflooding is commonly used due to its availability, cost effectiveness and simplicity. Radioactive tracer was introduced to get the optimum Residence Time Distribution (RTD) model which indicates the mechanism of the system. Radiotracer Gallium-68 (Ga-68) is a positron emitting radioactive material, which is eluted from parent Germanium-68 (Ge-68) generator to study the water flooding activity inside the 15 μm grain size of sand pack column oil recovery study. The sand was cleaned, occupying a Perspex sand pack column of 30 cm length and 5 cm diameter arranged in vertical position. The water inlet and tracer were injected from the bottom of the column, assisted by a syringe pump, with the flow rate optimized at 3.5 ml/min in order to push the saturated oil inside the column. Four Sodium Iodide (NaI) scintillation detectors were installed accordingly and attached to 12-channel data analyzer (DAS) to acquire signals of the emitted positron from the Ga-68 solution and monitored by a laptop. The activity utilized was 766 μCi/3ml and the half-life of Ga-68 was 68 minutes with penetrative energy of 511 keV. Initial experience of using Ga-68 was eluting it with 0.05 M HCl for 90μCi/3ml and directly inject it using pulse injection at the upstream of the column. Nonetheless, there was no indication of tracer arrival at the output after several hours which indicated the sole Ga-68 behaves as sand tracer thus, some modification was made to the respective Ga-68 solution. Chelating with DOTA-NHS solution was the second experience with Ga-68, which produced satisfactory result. A very vivid signal was retrieved at the output and RTD model analysis was carried out. The results indicated that the vertical sand pack column behaved as a Perfect Mixer with Parallel Model.